2019
DOI: 10.30595/hmj.v2i1.4204
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFIKASI LARVA LALAT DALAM KEPENTINGAN POST MORTEM INTERVAL PADA BANGKAI TIKUS (Rattus novergicus) YANG DIBERI CIU OPLOSAN DI SCIENCE TECHNO PARK UNIVERSITAS MUHAMMADIYAH PURWOKERTO

Abstract: Ciu merupakan salah satu minuman tradisional Banyumas yang mengandung alkohol. Ciu dapat dibuat oplosan dengan bahan lain untuk meningkatkan cita rasa dan sensasi minuman, namun berdampak buruk bagi kesehatan bahkan dapat menyebabkan kematian. Serangga berperan penting dalam penentuan Post Mortem Interval. Adanya kandungan obat atau senyawa yang terdapat pada jenazah dapat mempengaruhi perkembangan larva lalat. Tujuan penelitian ini untuk mengetahui spesies larva lalat yang terdapat pada bangkai tikus yang dib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
2
2
Order By: Relevance
“…The few number of this species larvae could be due to the organophosphates content in the carcass causing the development of these larvas were disrupted so that only a few larvae were found. The results of this study are different from the research conducted by Wardhani and Mulyanto (2019) which found that the larvae of C. bezziana were quite abundant. This difference could be due to organophosphate poison and ciu oplosan contain different compounds.…”
Section: Abundance Of Fly Larva In White Rat Carcasscontrasting
confidence: 99%
See 4 more Smart Citations
“…The few number of this species larvae could be due to the organophosphates content in the carcass causing the development of these larvas were disrupted so that only a few larvae were found. The results of this study are different from the research conducted by Wardhani and Mulyanto (2019) which found that the larvae of C. bezziana were quite abundant. This difference could be due to organophosphate poison and ciu oplosan contain different compounds.…”
Section: Abundance Of Fly Larva In White Rat Carcasscontrasting
confidence: 99%
“…This indicates that Sarcophagidae are more resistant to similar poisons. This is different from the research conducted by Wardhani and Mulyanto (2019), which used a ciu oplosan a traditional beverage (alcoholic beverages mixed with other ingredients) found that the type of fly larvae was dominated by the Calliphoridae family. This explains that the content of the type of poison used can affect the abundance of fly larvae on the carcass.…”
Section: Abundance Of Fly Larva In White Rat Carcasscontrasting
confidence: 88%
See 3 more Smart Citations